Correlation of the modified dental anxiety scale value with salivary alpha-amylase in pre-odontectomy patients - Wulansari, Daisy; Hadikrishna, Indra; Syamsudin, Endang (Padjadjaran Journal of Dentistry, 2020)
Introduction: Odontectomy is a minor surgical procedure that often results in dental anxiety. Dental anxiety can interfere during odontectomy treatment. Dental anxiety can be examined using the Modified Dental Anxiety Scale (MDAS) and through the level of the salivary alpha-amylase enzyme, both of which are dental anxiety biomarkers. The objective of this study was to analyse the correlation between anxiety values with salivary alpha-amylase levels using MDAS as an indicator of anxiety in pre-odontectomy patients. Methods: This study was conducted on 60 research samples of women aged 18-40 years who came to the minor surgery clinic of Department of Oral and Maxillofacial Surgery, Universitas Padjadjaran Dental Hospital, to have odontectomy treatment of maxillary or mandibular third molars impaction, not having systemic and oral diseases, and willing to participate in this study. Patients who met the inclusion criteria then required to sign the research consent statement; afterwards, the MDAS data was taken. The salivary alpha-amylase enzyme data was taken using the Cocoro meter (Nipro, Japan) tip which was kept under the tongue for 30 seconds, then the tip was inserted into the monitor, and the enzyme levels would be counted. The data obtained will be analysed using the Spearman rank correlation test. Results: The results showed that there was a significant relationship (p < 0.01) with a strong positive correlation (r = 0.85). Conclusion: There is a correlation between MDAS value and salivary alpha-amylase enzyme as an indicator of dental anxiety.